β-Keto and β-hydroxyphosphonate analogs of biotin-5’-AMP are inhibitors of holocarboxylase synthetase - Sittiwong, Wantanee (Bioorg Med Chem Lett, 2014)
Holocarboxylase synthetase (HLCS) catalyzes the covalent attachment of biotin to cytoplasmic and mitochondrial carboxylases, nuclear histones, and over a hundred human proteins. Nonhydrolyzable ketophosphonate (β-ketoP) and hydroxyphosphonate (β-hydroxyP) analogs of biotin-5′-AMP inhibit holocarboxylase synthetase (HLCS) with IC50 values of 39.7 μM and 203.7 μM. By comparison, an IC(50) value of 7 μM was observed with the previously reported biotinol-5'-AMP. The K(i) values, 3.4 μM and 17.3 μM, respectively, are consistent with the IC(50) results, and close to the K(i) obtained for biotinol-5'-AMP (7 μM). The β-ketoP and β-hydroxyP molecules are competitive inhibitors of HLCS while biotinol-5'-AMP inhibited HLCS by a mixed mechanism.